Early Use of Phenol Neurolysis Likely Reduces the Total Amount of Botulinum Toxin in Management of Post-Stroke Spasticity - Li, Sheng; Woo, Jean; Mas, Manuel F. (Frontiers in Rehabilitation Sciences, 2021)
The main objective was to examine practice patterns of phenol neurolysis for post-stroke spasticity management in the early stage. We performed a chart review of patients who were admitted for inpatient rehabilitation within 6 months after first-ever stroke and received phenol neurolysis within 15 months post-stroke. Out of 2367 stroke admissions from January 2014 and December 2018, 68 patients met the criteria. 52.9% of these patients received phenol neurolysis within 12 weeks, i.e., early stage. The earliest phenol neurolysis procedure was at 19 days after stroke. On average, patients received first phenol injections at 16.3 weeks after stroke with an average dose of 7.3 ml. Most commonly injected nerves were tibial nerve motor branches (41/68), sciatic nerve motor branches (37/68), lateral pectoral nerve (16/68), medial pectoral nerve (15/68), obturator nerve (15/68) and musculocutaneous nerve (15/68). Among 68 patients, 24 received phenol only; 17 received phenol neurolysis first followed by botulinum toxin (BoNT) injections; 19 received BoNT injections first followed by phenol neurolysis; 8 received both phenol and BoNT injections at the same time. The interval from stroke to first procedure was similar between the Phenol-First group (13.3 weeks) and the BoNT-First group (12.6 weeks). The total amount of BoNT was significantly lower in the Phenol-First group (361.3 units) than in the BoNT-First group (515.8 units) (p=0.005). The total amount of phenol was not statistically different between the Phenol-First group (5.9ml) and the BoNT-First group (8.3ml). The interval between the first procedure and its subsequent procedure was not statistically different between the Phenol-First group (18.3 weeks) and the BoNT-First group (10.7 weeks). These long intervals suggest that the subsequent injection (type and dose) was not planned during the first procedure. The general patterns of target areas were similar between BoNT injections and phenol neurolysis, except that phenol neurolysis rarely targeted the upper extremity distal muscles. No side effects after phenol or BoNT injections in the early stage after stroke were observed in the chart review. In summary, Early use of phenol neurolysis likely decreases the total amount of BoNT for management of post-stroke spasticity without increased side effects.